The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.4319/lo.2003.48.1.0141
|View full text |Cite
|
Sign up to set email alerts
|

In situ feeding and element removal in the symbiont‐bearing sponge Theonella swinhoei: Bulk DOC is the major source for carbon

Abstract: The vast majority of organic matter in the world ocean is found in the dissolved pool. However, no evidence has been demonstrated for direct uptake of bulk dissolved organic matter (DOM) by organisms other than bacteria and some invertebrate larvae. The total organic carbon (TOC) is 10-30% higher in coral reefs than in adjacent open waters. The dissolved organic carbon (DOC) accounts for Ͼ90% of the TOC. Using a new in situ technique for clean sampling of the seawater inhaled and exhaled by benthic suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
341
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(384 citation statements)
references
References 45 publications
23
341
3
Order By: Relevance
“…As organisms increase in size, SA/V drops and osmotrophy alone becomes insufficient to meet nutrient demands. Thus, strictly osmotrophic organisms tend to be microscopic (e.g., bacteria), although some macroscopic animals, including sponges, corals, brachiopods, bryozoans, molluscs, and echinoderms, use osmotrophic feeding on DOC as a supplemental food source (22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…As organisms increase in size, SA/V drops and osmotrophy alone becomes insufficient to meet nutrient demands. Thus, strictly osmotrophic organisms tend to be microscopic (e.g., bacteria), although some macroscopic animals, including sponges, corals, brachiopods, bryozoans, molluscs, and echinoderms, use osmotrophic feeding on DOC as a supplemental food source (22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Corals may rapidly consume DOC and bacterioplankton (Sorokin, 1973), although many recent studies show corals to be sources, rather than sinks, for DOC (Ferrier-Pages et al, 1998;Van Duyl and Gast, 2001;Hata et al, 2002;Nakajima et al, 2009). Recent work has demonstrated the potential for sponges to consume both DOC and bacterioplankton at biogeochemically significant rates (Yahel et al, 2003;Van Duyl et al, 2006;de Goeij and Van Duyl, 2007;De Goeij et al, 2008). However, conspicuous sponge taxa, which exhibit the highest filtration rates (Southwell et al, 2008), are virtually absent from our study area, and even inconspicuous benthic sponges cover o1% of the reef benthos in Moorea on average (Adjeroud, 1997, http://mcr.…”
Section: Discussionmentioning
confidence: 99%
“…Al− though typical sponges feed primarily on bacterial−sized parti− cles through the microvilli of their choanocytes (e.g., Reiswig 1971;Riisgård and Larsen 2000), in some cases (Leys and Eerkes−Medrano 2006) particle capture is through pseudo− podial extensions of these cells; larger particles (5-50 μm) are often captured by amoebocytes lining the incurrent canal walls (Reiswig 1971). There has also been an increasing apprecia− tion of the role of direct uptake of dissolved organic carbon (e.g., Reiswig 1981;Yahel et al 2003), but it is not yet clear to what extent symbiotic organisms are responsible for the up− take, and if the sponge itself is responsible, what is the mecha− nism of uptake. Other studies have also shown that sponge growth rate is independent of the supply of Dissolved Organic Carbon, suggesting a greater dependence on solid particle consumption (Koopmans and Wijffels 2008).…”
Section: Discussionmentioning
confidence: 99%